2017
DOI: 10.1523/jneurosci.0867-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Early Procedural Pain Is Associated with Regionally-Specific Alterations in Thalamic Development in Preterm Neonates

Abstract: Very preterm human neonates are exposed to numerous invasive procedures as part of life-saving care. Evidence suggests that repetitive neonatal procedural pain precedes long-term alterations in brain development. However, to date the link between pain and brain development has limited temporal and anatomic specificity. We hypothesized that early exposure to painful stimuli during a period of rapid brain development, before pain modulatory systems reach maturity, will predict pronounced changes in thalamic deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
173
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 62 publications
(44 reference statements)
8
173
1
3
Order By: Relevance
“…Studies designed to investigate the contribution of such stressors to the long-term effects of PTB are difficult, because of the presence of multiple confounders such as illness severity or length of the NICU stay. Nevertheless, studies which have attempted to correct for various confounders have shown that the number of painful procedures experienced associates with alterations in brain development [15][16][17] suggesting that some stressors may indeed have long term consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies designed to investigate the contribution of such stressors to the long-term effects of PTB are difficult, because of the presence of multiple confounders such as illness severity or length of the NICU stay. Nevertheless, studies which have attempted to correct for various confounders have shown that the number of painful procedures experienced associates with alterations in brain development [15][16][17] suggesting that some stressors may indeed have long term consequences.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that the plasticity of the infant brain is even more vulnerable to the exposure to illness and the environment in neonatal intensive care. Neonatal pain‐related stress in very preterm infants is associated with altered brain cortical thickness at school age and has been shown to contribute to slower growth of thalamus associated with poorer cognitive and motor outcome at 3 years of age . An association has been found between neonatal pain‐related stress and hair cortisol in preterm boys at school age, suggesting the early programming effect downregulating the HPA axis response to psychosocial stress in preterm children several years after prenatal and postnatal stressors had been terminated .…”
Section: Introductionmentioning
confidence: 99%
“…Disruption in this developmental process might cause neural apoptosis [Anand et al, 2007;Dührsen et al, 2013] and altered development of thalamocortical axons [Dean et al, 2013;Molnar and Rutherford, 2013]. Moreover, very preterm infants present abnormal myelinization and fractional anisotropy in gray and white matter areas [Dubois et al, 2008;Eaton-Rosen et al, 2015], decreased cortical and subcortical gray matter volume [Dubois et al, 2008;Eaton-Rosen et al, 2015], decreased cortical and subcortical gray matter volume Chau et al, 2019], thalamocortical alterations [Ball et al, 2012;Cai et al, 2017] and pain-induced volume reduction of white matter and subcortical gray matter [Brummelte et al, 2012;Duerden et al, 2018]. These structural alterations persist into school age [Hohmeister et al, 2010;Lax et al, 2013] and adulthood [Menegaux et al, 2017;Nosarti et al, 2014] and are associated with lower IQ [Breeman et al, 2017;Nosarti et al, 2014].…”
Section: Introductionmentioning
confidence: 99%